RNA metagenomic profiling of mosquito viromes associated with Vector-Borne diseases in Quebec, Canada - Ines Levade; Benjamin Delisle; Éric Fournier; Christian Therrien (PLoS ONE, 2026)
Mosquitoes harbor diverse viral communities, including both medically important arboviruses and insect-specific viruses, yet the viromes of mosquito populations in northern temperate regions remains poorly characterized. In this study, we used metagenomic sequencing to analyse pools of archived mosquito samples from Québec, Canada representing multiple species previously identified as arbovirus carriers. Our analyses identified 60 viral species, including three arboviruses, several insect-specific viruses, and multiple dual-host non-pathogenic viruses, revealing the rich viral diversity present in these mosquito populations. Phylogenetic analysis of complete viral genomes demonstrated genetic relationships with viruses reported from diverse geographic regions. We describe, a newly proposed bipartite Culex tombus- like virus and report the complete resolution of thirty-five viral genomic sequences. These results highlight the utility of metagenomic approaches for comprehensive characterization of the mosquito virome and underscore their potential to enhance surveillance of emerging arboviruses, including West Nile virus, in Québec and similar northern ecosystems.